Palladium electrodissolution from model surfaces and nanoparticles - Pizzutilo, Enrico; Geiger, Simon; Freakley, Simon J.; Mingers, Andrea; Cherevko, Serhiy; Hutchings, Graham J.; Mayrhofer, Karl (Electrochimica Acta, 2017)
Palladium (Pd) is considered as a possible candidate as catalyst for proton exchange membrane fuel cells (PEMFCs) due to its high activity and affordable price compared to platinum (Pt). However, the stability of Pd is known to be limited, yet still not fully understood. In this work, Pd dissolution is studied in acidic media using an online inductively coupled plasma mass spectrometry (ICP-MS) in combination with an electrochemical scanning flow cell (SFC). Crucial parameters influencing dissolution like potential scan rate, upper potential limit (UPL) and electrolyte composition are studied on a bulk polycrystalline Pd (poly -Pd). Furthermore, a comparison with a supported high -surface area catalyst is carried out for its potential use in industrial applications. For this aim, a carbon supported Pd nanocatalyst (Pd/C) is synthesized and its performance is compared with that of bulk poly -Pd. Our results evidence that the transient dissolution is promoted by three main contributions (one anodic and two cathodic). At potentials below 1.5 VRHE the anodic dissolution is the dominating mechanism, whereas at higher potentials the cathodic mechanisms prevail. On the basis of the obtained results, a model is thereafter proposed to explain the transient Pd dissolution.(C) 2017 Elsevier Ltd. All rights reserved.
Keywords: palladium; dissolution; ORR catalyst; ICP-MS; PEMFC